Hubungan Peran Ibu dengan Pengetahuan Siswi tentang Menstrual Hygiene di Sekolah Dasar Wilayah Kelurahan Salaman - Lukita, Salsabila Arum; Susanti, Dwi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Jenderal Achmad Yani Yogyakarta, 2024)
Background : Menstruation is a sign of puberty in women and requires proper management to prevent health and social problems. Lack of knowledge can cause problems with mothers playing a crucial role in menstrual education. Mothers are one of the first sources of information on menstrual hygiene. Objective : To find out the relationship between the role of mothers and students' knowledge about menstrual hygiene at the Salaman Village Regional Elementary School. Methods : Quantitative research with correlational descriptive design with an approach cross sectional. Use Total sampling Where the sample taken was 33 respondents, the measuring tools used were the mother's role questionnaire and the knowledge questionnaire menstrual hygiene, with a test Somers'd. Results : The results were obtained from 33 respondents aged 11 years as many as 17 respondents (51.5), the most menstruating age was 10 years old as many as 20 respondents (60.6%), the most respondents were class VI as many as 18 respondents (54.5%), the most respondents were 31-40 years old as many as 25 respondents (75.8%), the last education of the most respondents was high school as many as 22 respondents (66.7%), with 19 respondents (57.6%) entering the good category of motherhood and as many as 15 respondents (45.5%) entering the knowledge menstrual hygiene enough. Conclusion : There is a relationship between the role of mothers and the knowledge of female students about menstrual hygiene at the Elementary School in sekolah dasar wilayah kelurahan salaman with p-value 0,013 (p<0.05).